2017
DOI: 10.1002/adem.201700201
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed Roll‐to‐Roll Hot Embossing of Micrometer and Sub Micrometer Structures Using Seamless Direct Laser Interference Patterning Treated Sleeves

Abstract: In this study, we present a seamless high-speed roll-to-roll hot embossing process using a direct laser interference patterned nickel sleeve as a mold. Line-like patterns with spatial periods of 5.0, 3.9, and 1.5 mm and structure heights of 572, 325, and 141 nm, respectively are used for imprinting PET-foils. The influence of the web speed on the cavity filling and consequently on the structure height and homogeneity of the fabricated patterns is studied. The web speed is varied between 2 and 50 m min À1 . For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Other authors report similar fluence values for ablation of nickel. 0.36 J/cm 2 was used for DLIP with a laser of 1064 nm wavelength and 10 ps pulse duration 47 . Using longer pulses of 6 ns and 1053 nm wavelength, 2.2 J/cm 2 fluence was selected by 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors report similar fluence values for ablation of nickel. 0.36 J/cm 2 was used for DLIP with a laser of 1064 nm wavelength and 10 ps pulse duration 47 . Using longer pulses of 6 ns and 1053 nm wavelength, 2.2 J/cm 2 fluence was selected by 48 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it serves as an indicator that during the hot embossing process, even the deepest cavities of the sleeve could be filled by the soft polymer. [37,38] In addition, it is demonstrated that the obtained foil has a hierarchical topography with threelevel scales, namely the DLIP-produced grooves and the selforganized LSFL and HSFL. The optical effects of these microand nanostructures are addressed in the following sections.…”
Section: Patterned Polyethylene Terephthalate Foilsmentioning
confidence: 96%
“…[33][34][35][36] In contrast to these methods, direct laser interference patterning (DLIP) is a one-step processing technique able to structure seamless sleeves with feature sizes below 1 μm and at processing speeds already reaching 57 cm 2 min À1 . [37][38][39] In this method, two or more coherent laser beams are overlapped on the sample surface resulting in a periodical intensity distribution within the interference volume. If the absorbed laser energy is high enough, the material is locally removed, producing a repetitive surface pattern with a spatial period in the typical range from 500 nm to 10 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Mold texturing for injection molding applications requires a high speed and flexibility [24]. Laser patterning has been proven effective for the fast-engraving of highly uniform micro-structured surfaces on a large variety of materials, including steel [25][26][27]. Furthermore, throughputs as high as 1 cm 2 per 10 s have been reported for metals when producing self-organized sub-micron structures [28].…”
Section: Introductionmentioning
confidence: 99%